Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/em.21960
|View full text |Cite
|
Sign up to set email alerts
|

MRP1 expression in bronchoalveolar lavage cells in subjects with lung cancer who were chronically exposed to arsenic

Abstract: Alteration of multidrug resistance-associated protein-1 (MRP1) expression has been associated with certain lung diseases, and this protein may be pivotal in protecting the lungs against endogenous or exogenous toxic compounds. The aim of this study was to evaluate and compare the expression of MRP1 in bronchoalveolar cells from subjects with and without lung cancer who had been chronically exposed to arsenic through drinking water. MRP1 expression was assessed in bronchoalveolar cells in a total of 102 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…In Mexico, a case-control study investigated whether As could influence multidrug resistance-associated protein-1 (MRP1) expression, which has a protective role against arsenic. This study demonstrated significant reduction of MRP1 expression in bronchoalveolar lavage (BAL) cells in lung cancer patients with levels of >50 μg/L when compared with the controls with similar As levels (p=0.02) (Recio-Vega et al, 2015a). This may increase intracellular toxic compounds in lung cells, increasing lung cancer risk.…”
Section: Lung Cancermentioning
confidence: 72%
“…In Mexico, a case-control study investigated whether As could influence multidrug resistance-associated protein-1 (MRP1) expression, which has a protective role against arsenic. This study demonstrated significant reduction of MRP1 expression in bronchoalveolar lavage (BAL) cells in lung cancer patients with levels of >50 μg/L when compared with the controls with similar As levels (p=0.02) (Recio-Vega et al, 2015a). This may increase intracellular toxic compounds in lung cells, increasing lung cancer risk.…”
Section: Lung Cancermentioning
confidence: 72%
“…Lindberg et al [] reported that in a population from Bangladesh gender and age were major factors influencing As metabolism, and that women had higher As methylation efficiency than men. However, sexual difference in As methylation capacity was not observed in other studies [Chiou et al, ; Kurttio et al, ; Chen et al, ; Recio‐Vega et al, ]. This gender difference in As methylation capacity could be explained in part by the effect of estrogen.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, these efflux proteins contribute to the many physiological and pathophysiological processes influenced by these compounds, including oxidative stress. In a previous study, we reported a negative correlation between MRP1 expression and chronic arsenic exposure in subjects with lung cancer (Recio‐Vega et al, 2015). Several studies evaluating the effects of polymorphism of both efflux pumps on their function have been reported.…”
Section: Introductionmentioning
confidence: 73%
“…A cross‐sectional study was carried out, and participants were recruited from the Department of Respiratory Diseases, Mexican Institute of Social Security, Torreon, Coahuila, Mexico. The volunteers were residents of the Comarca Lagunera where higher arsenic tap water levels have been detected in the last 32 years, ranging from 10.4 to 360 ppb in 2015 (Recio‐Vega et al, 2015). The geographic area received groundwater through the local water supply, and the high As levels in the water are due, in part, to an overextraction of water from the ground for crops.…”
Section: Methodsmentioning
confidence: 99%